\sqrt[3]{n^3+3n}-\sqrt{n^2-2n}= \sqrt[6]{(n^3+3n)^2}- \sqrt[6]{(n^2-2n)^3}=a^{1/6}-b^{1/6} , donde a=(n^3+3n)^2, b=(n^2-2n)^3
Simplifiquemos primero a^{1/6}-b^{1/6} . Tenga en cuenta que a^{1/6}-b^{1/6}=\frac{a^{1/3}-b^{1/3}}{a^{1/6}+b^{1/6}}=\frac{(a^{1/3})^3-(b^{1/3})^3}{(a^{1/6}+b^{1/6})(a^{2/3}+a^{1/3}b^{1/3}+b^{2/3})}=\frac{a-b}{(a^{1/6}+b^{1/6})(a^{2/3}+a^{1/3}b^{1/3}+b^{2/3})}
El numerador es a-b=n^6\left ((1+\frac 3{n^2})^2-(1-\frac 2n)^3\right)=n^6(6/n+ 9/n^4+8/n^3-18/n^2)
1 factor en el denominador = n\left((1+\frac 3n)^{1/3}+(1-\frac 2n)^{1/2}\right)
2 nd factor en el denominador= n^4\left ( (1+\frac 3{n^2})^{4/3}+(1+\frac 3{n^2})^{2/3}(1-\frac 2n)+(1-\frac 2n)^{1/2}\right)
Así que tenemos
\begin{align}\sqrt[3]{n^3+3n}-\sqrt{n^2-2n}&= \sqrt[6]{(n^3+3n)^2}- \sqrt[6]{(n^2-2n)^3}\\&=a^{1/6}-b^{1/6}\\&=\frac{6+\frac 1{n^3}(9+8n-18n^2)}{\left((1+\frac 3n)^{1/3}+(1-\frac 2n)^{1/2}\right)\left ( (1+\frac 3{n^2})^{4/3}+(1+\frac 3{n^2})^{2/3}(1-\frac 2n)+(1-\frac 2n)^{1/2}\right)}\\& \to\frac {6} {2\times 3}=1\end {align}